Deep Eutectic Supramolecular Polymers: Bulk Supramolecular Materials. Issue 29 (11th May 2020) - Wu, Shuanggen; Cai, Changyong; Li, Fenfang; Tan, Zhijian; Dong, Shengyi
Abstract: Application of new strategies for supramolecular self‐assembly can significantly impact the properties and/or functions of supramolecular polymers. To realize a facial strategy for the development of solvent‐free supramolecular polymers in bulk, "deep eutectic solvents" were employed. Cyclodextrins and natural acids were used to prepare deep eutectic supramolecular polymers (DESP s). Deep eutectic solvents have special characteristics that endow DESP s with unique macroscopic properties and excellent processability. DESP s exhibit supramolecular adhesion and temperature‐dependent behavior originating from the combined effects of deep eutectic solvents and supramolecular polymerization. Because DESP s are solvent‐free and display interesting macroscopic properties, they have potential as new adaptive materials. Abstract : Go deep : Deep eutectic supramolecular polymers were developed as a new type of bulk supramolecular material. They exhibit supramolecular adhesion and temperature‐dependent behavior originating from the combined effects of deep eutectic solvents and supramolecular polymerization. These polymers also demonstrate potential as powerful supramolecular adhesive materials.